Brief overview of allochtonous phosphorus load on cascade reservoirs in Citarum River Basin, West Java Indonesia. Issue 1 (1st July 2022) - Lukman, L; Kartamihardja, ES; Hariyadi, S; Sunardi,; Sumiarsa, D
Abstract: The Citarum River, Indonesia, has undergone degradation due to the pollutants, including phosphorus, that enters the river and the reservoirs of Saguling, Cirata, and Juanda (The official name of Jatiluhur Reservoir). The observations of total phosphorus (TP) load instantaneously had been carried out on the three reservoirs and TP measurements from 8 to 12 August 2019. The TP concentration in the inlets was generally very high (> 0.3 mg L -1 ), whereas the average TP concentration in Saguling, Cirata, and Juanda Reservoirs was 0.378 mg L -1, 0.343 mg L -1, and 0.324 mg L -1, respectively. Based on the trophic criteria, the condition of the waters in the three reservoirs was hypertrophic. Meanwhile, the average TP level in the Saguling showed the highest level compared to other reservoirs, which is in line with the TP concentration that enters the Saguling Reservoir, which is generally very high. Based on the instantaneous inputs, the loading TP to Saguling, Cirata, and Juanda Reservoirs were 26.471 g sec -1, 36.241 g sec -1, and 55.573 g sec -1, respectively. This indicates that the loading of phosphorus from upstream to downstream tends to increase.